2015
DOI: 10.1021/acschemneuro.5b00179
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Inward Opening of the Dopamine Transporter Is Triggered by PIP2-Regulated Dynamics of the N-Terminus

Abstract: We present the dynamic mechanism of concerted motions in a full-length molecular model of the human dopamine transporter (hDAT), a member of the neurotransmitter/sodium symporter (NSS) family, involved in state-to-state transitions underlying function. The findings result from an analysis of unbiased atomistic molecular dynamics simulation trajectories (totaling >14 μs) of the hDAT molecule immersed in lipid membrane environments with or without phosphatidylinositol 4,5-biphosphate (PIP2) lipids. The N-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
163
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(178 citation statements)
references
References 97 publications
15
163
0
Order By: Relevance
“…Indeed, studies of LeuT and other related bacterial transporters162233 have proposed that an occupied Na2 site is essential for maintaining the transporter in the inward-closed state and that inward-opening and the subsequent substrate release process are energetically more favorable once the Na + ion has left the Na2 site. Consistent with this model, MD simulations of DAT28 and SERT31 have displayed spontaneous outward-open to inward-open transition upon destabilization and inward release of the sodium from the Na2 site. From analysis of microsecond-long MD trajectories28 we discovered that the release of the sodium from the Na2 site (referred to hereafter as Na + /Na2) in the human DAT (hDAT) can be allosterically triggered by interactions of the N-terminus region of the transporter (residues 1–59) with various other regions of the transporter, and that some of these interactions are electrostatically driven and supported by the highly charged (−4e at neutral pH) PI(4,5)P 2 (phosphatidylinositol 4,5-biphosphate) lipids in the membrane283435.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Indeed, studies of LeuT and other related bacterial transporters162233 have proposed that an occupied Na2 site is essential for maintaining the transporter in the inward-closed state and that inward-opening and the subsequent substrate release process are energetically more favorable once the Na + ion has left the Na2 site. Consistent with this model, MD simulations of DAT28 and SERT31 have displayed spontaneous outward-open to inward-open transition upon destabilization and inward release of the sodium from the Na2 site. From analysis of microsecond-long MD trajectories28 we discovered that the release of the sodium from the Na2 site (referred to hereafter as Na + /Na2) in the human DAT (hDAT) can be allosterically triggered by interactions of the N-terminus region of the transporter (residues 1–59) with various other regions of the transporter, and that some of these interactions are electrostatically driven and supported by the highly charged (−4e at neutral pH) PI(4,5)P 2 (phosphatidylinositol 4,5-biphosphate) lipids in the membrane283435.…”
supporting
confidence: 57%
“…They have offered an essential molecular context for the investigation of the mechanism of uphill neurotransmitter reuptake transport enabled by the coupling with the transmembrane Na + gradient110. Our current understanding of functional mechanisms in NSS has been further shaped by the large body of structure-function studies of LeuT and other related bacterial transporters, carried out both experimentally11121314151617 and computationally1112131416181920212223, and more recently by findings from molecular dynamics (MD) simulations of DAT242526272829 and SERT3031 constructs. Together, these studies have suggested for the transport cycle in NSS proteins an allosteric process that is consistent with the alternating access mechanism32 in which concerted dynamic rearrangements on the extracellular (EC) and intracellular (IC) sides of the transporter result from ion- and ligand-specific conformational rearrangements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism would enable the kinase-dependent phosphorylation required for the amphetamine-induced reverse transport of the substrate, which is, in turn, responsible for the psychostimulant effect. Moreover, subsequent simulations on DAT have shown that PIP2 is able to trigger the inward-open state and hence ions/substrate release, by contacting, among the others, residue R443 on IL4, which is conserved in SERT (K460), and K352 (IL3) [32]. However, experimental evidence has also demonstrated that depletion of this lipid does not affect physiological substrate reuptake, neither in SERT nor in DAT [30, 31], suggesting that direct and reverse transport may be independently managed by membrane machinery [32].…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, recent studies have been carried out on both LeuT- and d DAT-based homology models to investigate the effects of h DAT missense mutations on the onset of brain diseases [29]. A similar conclusion can be drawn the investigation of NSSs-lipid interactions, where the above mentioned homology models have found broad application [3032]. …”
Section: Introductionmentioning
confidence: 91%